2020
DOI: 10.3389/fnsyn.2020.00024
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal-Ventral Differences in Modulation of Synaptic Transmission in the Hippocampus

Abstract: Functional diversification along the longitudinal axis of the hippocampus is a rapidly growing concept. Modulation of synaptic transmission by neurotransmitter receptors may importantly contribute to specialization of local intrinsic network function along the hippocampus. In the present study, using transverse slices from the dorsal and the ventral hippocampus of adult rats and recordings of evoked field postsynaptic excitatory potentials (fEPSPs) from the CA1 stratum radiatum, we aimed to compare modulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 128 publications
(222 reference statements)
6
12
0
Order By: Relevance
“…Different regions of the hippocampus appear to be engaged in different cognitive activities ( Shors et al, 2002 ; Bannerman et al, 2004 ; Fanselow and Dong, 2010 ; Strange et al, 2014 ; Huckleberry et al, 2018 ; Trompoukis and Papatheodoropoulos, 2020 ). It is suggested that the dorsal hippocampus may perform primarily cognitive functions, whereas the ventral part is more related to the processing of stress, emotion and affect ( Fanselow and Dong, 2010 ; Kheirbek and Hen, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different regions of the hippocampus appear to be engaged in different cognitive activities ( Shors et al, 2002 ; Bannerman et al, 2004 ; Fanselow and Dong, 2010 ; Strange et al, 2014 ; Huckleberry et al, 2018 ; Trompoukis and Papatheodoropoulos, 2020 ). It is suggested that the dorsal hippocampus may perform primarily cognitive functions, whereas the ventral part is more related to the processing of stress, emotion and affect ( Fanselow and Dong, 2010 ; Kheirbek and Hen, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…They exhibit differential rates of neurogenesis and each displays a distinct pattern of neurotransmitter receptor distribution [ 155 , 156 , 157 ]. In addition, the septal/temporal divisions of the hippocampus exhibit significant differences in behavior-induced arc gene expression [ 158 ], distinct transcriptional and epigenetic effects in response to an enriched environment or physical activity [ 82 , 159 ], and distinct pathological responses throughout aging [ 160 ]. The dorsal hippocampus is associated with spatial memory and contextual information processing, while the ventral hippocampus is related to emotional behavior in association with fear, anxiety, and reward processing [ 161 , 162 , 163 ].…”
Section: Differential Effects Of Sedentary Lifestyle and Masticatory ...mentioning
confidence: 99%
“…Astrocyte morphology is affected by aging [ 160 , 168 , 169 , 170 , 171 , 172 ], enriched environment [ 41 , 173 ] and masticatory dysfunctions [ 27 ], in a region- and subregion-specific manner. However, our previous astrocyte analysis related to masticatory dysfunction, age and sedentary lifestyle did not explore the septal-temporal (dorsoventral) hippocampal division.…”
Section: Differential Effects Of Sedentary Lifestyle and Masticatory ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Early anatomical studies demonstrated differences between the afferent and efferent nerve projections of the dorsal hippocampus (dHPC) and ventral hippocampus (vHPC) (Swanson and Cowan, 1977). According to a current consensus, the role played by the most dorsally located hippocampal segment is on cognitive operations like spatial navigation, while internally monitoring functions related to emotionality are taken on by the ventral segment of the hippocampus (Trompoukis and Papatheodoropoulos, 2020). Moreover, some studies have found that caffeine reverts memory impairment in a depression-prone mouse strain with upregulation of adenosine A 2A receptors in the hippocampus (Machado et al, 2017), while selective A 2A R knockout in the forebrain region (striatum, hippocampus, and cortex) induces anxiety-like behavior (Wei et al, 2014).…”
Section: Introductionmentioning
confidence: 99%